Violence against children and adolescents: nurse's actions in primary health care - Emanuella de Castro Marcolino; Renata Clemente dos Santos; Francisco de Sales Clementino; Rafaella Queiroga Souto; Glauber Weder dos Santos Silva; Francisco Arnoldo Nunes de Miranda (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to analyze the role of nurses in suspected or confirmed cases of violence against children and adolescents in Primary Health Care. Methods: an analytical research, with a qualitative approach. Thirty nurses participated in the study, and data were collected by means of an individual form and a semi-structured interview. The data received lexicographic analysis by the software IRaMuTeQ (Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires) organized by Bardin's content analysis. Results: five categories emerged, in which it was possible to consider that the nurses' approach in cases of violence was based on the identification of violence through physical examination during nursing consultations, health promotion actions in the school environment, request for support from the multi-professional team, and transfer of responsibilities. Final Considerations: it is inferred that the fragility in the professional training of nurses to address situations of violence against children and adolescents produces deficits in comprehensive care for victims.